Komu było dedykowane dzieło Gwagnina Sarmatiae Europeae descripto? - rozwiązanie zagadki znanego polonicum XVI w. - Wilgosiewicz-Skutecka, Renata (Biblioteka Uniwersytecka w Poznaniu, 2007)
This article addresses the problem of the original addressee of the dedication inscribed in the book entitled Sarmatiae Europeae descriptio by A. Gwagnin (Alessandro Guagnini). A unique copy of the book published in 1574 found by the author in Bibliothćque Mazarine in Paris has shed light on the question posed in the title. Gwagnin’s work was originally dedicated to Henry of Valois and it was only after the well-know string of historical events and his notorious flight from Poland (as he secretly left Poland to ascend the French throne) that the dedication was changed, on the initiative of the publisher, to that of Stephen Batory of Poland. This discovery changes the dating of the book adopted hitherto in available monographs and bibliographies.
To whom was the book Sarmatiae Europeae descriptio by A. Gwagnin dedicated? A solution of the puzzle of a well-known sixteenth-century material concerning Poland